2014
DOI: 10.15282/ijame.9.2013.30.0181
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Diesel Engine Performance for Castor and Jatropha Biodiesel-Blended Fuel

Abstract: Vegetable oils and their methyl/ethyl esters are alternative renewable fuels for compression ignition engines. Asian countries are not self-sufficient in edible oil and are exploring non-edible seed oils, like jatropha and castor as biodiesel raw materials. In the present study jatropha and castor oil were used for the preparation of biodiesel by the transesterification process. Diesel and jatropha oil methyl ester (JOME) blends were used to conduct short-term engine performance tests at varying loads. Similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…An observable reduction in power was observed in WCO B5, but it was not observed in RSO B5. According to Vashist and Ahmad [12], the resultant engine power produced from various types of biodiesel blends is generally lower than that of petrodiesel due to the reduction in calorific value; see Figure 3(a). Although the reduction in engine power and torque is minimal at 2400 rpm for biodiesel blends B5 and (a) (b) journal.ump.edu.my/jceib ◄ B10, respectively.…”
Section: Engine Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An observable reduction in power was observed in WCO B5, but it was not observed in RSO B5. According to Vashist and Ahmad [12], the resultant engine power produced from various types of biodiesel blends is generally lower than that of petrodiesel due to the reduction in calorific value; see Figure 3(a). Although the reduction in engine power and torque is minimal at 2400 rpm for biodiesel blends B5 and (a) (b) journal.ump.edu.my/jceib ◄ B10, respectively.…”
Section: Engine Test Resultsmentioning
confidence: 99%
“…For instance, Rahim et al [11] showed a negligible power reduction (ranging from 1.1 to 1.4%) in a diesel engine running on a 5% biodiesel blended fuel. Vashist and Ahmad [12] studied the performance of Jatropha and castor-seed-based biodiesel blends. They reported a minimum thermal power reduction at a blending ratio of 10%, but the power was markedly reduced at a 20% blending ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The jatropha can grow anywhere, suitable for all conditions. Based on the studies available it is the best substitute available at present to fossil fuel [15]. This paper presents experimental results of 100% JOME and 80%, 60%, 40% and also 20% JOME blends with diesel on the performance and emission characteristics of the engine.…”
Section: Introductionmentioning
confidence: 99%
“…The International Energy Agency, estimated that by the end of 2030, the net energy consumption will increase by more than 55% [3][4][5]. The Energy Information Administration (EIA) of the United States predicted that net petroleum products utilisation and consumption will increase from around 86 million barrels per day to 110 million barrels per day by the end of 2035 [6,7]. Due to the rapid depletion in conventional fuels, the rising price of petroleum products and major current environmental issues have gathered momentum in finding out a substitute, an alternative source of energy, which can replace the current conventional fuel in the future.…”
Section: Introductionmentioning
confidence: 99%